Exploring Islamic website features that influence user satisfaction: a conceptual model - Aliyu, Mansur; Mahmud, Murni; Md Tap, Abu Osman (Elsevier, 2012)
Islamic websites (I-Webs) demand special attention by the nature of the content they deliver to users. To deliver satisfying and useful content for Islamic activities online (e.g. learning about Islam, questioning scholars, chat), it is important to identify and understand the most important features an Islamic website should portray. In this paper, we conducted extensive web searches and reviewed the literature on Islamic websites in order to explore features that influence users to visit a website for online Islamic activities, consequently leading to user satisfaction. The features were categorized into design, content, and Islamic. Design features were measured by usability, navigation, functionality, accessibility, interactivity, attractiveness, and security/privacy. Content features were measured by trust, objectivity, credibility, reliability, relevance, legitimacy, and authority. Islamic features were measured by Tawhid (belief), Sunnah, (practice), Niyyah (intention), ethics, identity, symbols, and software. We conceptualized and proposed that these features influence the use of I-Web and consequently lead to user satisfaction. The conceptual model will provide direction for future empirical research on Islamic websites, which is currently lacking.